Developing Client Self-Advocacy in Occupational Therapy: Are We Practicing What We Preach? - Laura VanPuymbrouck; Emily M. Chun; Elizabeth D. Hesse; Kelsey Ranneklev; Camila Sanchez (Occupational Therapy International)
Background. Developing client self-advocacy is in occupational therapy’s (OT) scope of practice; however, there is limited understanding of if, or how, occupational therapists learn about self-advocacy interventions as well as implement self-advocacy into clinical practice. Objective. This study sought to identify if and how therapists learn about self-advocacy intervention approaches and identify if and how therapists implement self-advocacy into their work with clients. Method. A survey was distributed via email to academic and professional listservs in the United States, and data were collected using REDCap survey software. Descriptive statistics were analyzed data using REDCap/SPSS. Comparative statistics, Kruskal-Wallis’s tests, Chi-square tests for independence, and Pearson’s correlation tests analyzed differences across groups of respondents. Results. Practicing and licensed occupational therapists (n=138) across the United States completed the survey. Findings indicate a majority (59.5%) of occupational therapists not learning strategies for addressing or developing client self-advocacy. Of significance, 21.7% of participants had never been exposed to concepts of client self-advocacy in academic or clinical education. Practitioners who did address self-advocacy did so indirectly through teaching-related skills (76.6%). Conclusion. Many clients of OT will need self-advocacy skills in order to address issues of exclusion and discrimination that prohibit full participation in society. Occupational therapists must prioritize incorporating client self-advocacy into curricula and clinical practice.